FINANCIAL FEASIBILITY STUDY OF CONVERTING BONTANG LNG PLANT INTO LNG RECEIVING & REGASIFICATION FACILITY - Anindito Indriawan, Johan
Having trend of demand increases and production declines, Kalimantan’s natural gas production might not be adequate to fulfill all potential regional demands in the future. Without gas import into the region, several strategic industries that rely on gas might not survive in long term. Thanks to the existence of Bontang LNG Plant, importing gas into the region in the form of LNG is one step closer to be feasible. Conversion of Bontang LNG Plant into an LNG Receiving & Regasification Facility (“Bontang Regas”) is technically feasible at considerably less capital expenditure compared to grass root construction. The similar conversion was successfully performed in Arun LNG Plant back in 2014. Yet the financial feasibility of such conversion in Bontang needs to be evaluated. This study will elaborate the regional Kalimantan gas balance & potential future demand for gas import as well as prospect to source LNG from global market. This study will also evaluate the most appropriate business scheme for future Bontang Regas. And finally, the financial feasibility will be evaluated by developing financial model and projections of Income Statement, Balance Sheet, and Cash Flow Statement. According to the analysis, importing gas into the region will be needed after 2031. Sources of LNG will be abundantly available in the global market. The delivered gas price to Customers is predicted will be 85% cheaper than the price of substitute energy source, i.e. crude oil, even after considering fuel & fee associated to Regas Facility. The most recommended business scheme for Bontang Regas is “Fee Scheme”, where the company who run this business shall charge regasification fee to Customers who will purchase LNG directly from Suppliers. Bontang Regas business is economically feasible at the base case assumptions. The break-even regasification fee of 0.68 US$/MMBTU (for a given IRR 11% as imposed by regulation) will be very competitive in the market. The NPV to the firm, calculated by considering the cost of capital of 6.33%, is estimated 145.69 million US$ after an initial investment of 142 million US$. The firm’s profitability index is 3.6. Both NPV and profitability index satisfy the criteria for this investment to be feasible. The investment will be paid out in 6.9 years out of 15 years design operational lifetime. Risk analysis by monte-carlo simulation concludes that the business risk is considered as low. The probability of losing money is 1.4%. The riskier aspect of this project is the probability of less-than-predicted regasification demand, thus ensuring the accuracy of gas balance is very crucial before committing final investment decision.